The demand for foreign workers in the manufacturing sector in Malaysia - Nasri Bachtiar; Rahmi Fahmy; Rahmah Ismail (Penerbit Universiti Kebangsaan Malaysia, 2015)
The objective of this study is to investigate the demand for foreign workers in the manufacturing sector in Malaysia. In order to achieve this objective, the simultaneous equation model is developed and the analyses are based on data from the Industrial Survey conducted by the Department of Statistics Malaysia for the period of 1994-2005. The Labor demand model is derived from the Cobb-Douglas production function. The results from the estimation of the production function show that foreign workers in the category of professional significantly contributed to the output growth of ISIC 35, ISIC 36 and ISIC 38, while skilled workers and technical-supervisors also give a significant contribution to output growth in ISIC 31. The demand for foreign workers reveals that professionals and technical-supervisors are positively related to output level and wage rates. However, they are negatively related to the price of capital and local wage rate. It means that the professional and technical-supervisor foreign workers complement the local workers and capital.